2018
DOI: 10.1111/odi.12866
|View full text |Cite
|
Sign up to set email alerts
|

Early salivary changes in multiple myeloma patients undergoing autologous HSCT

Abstract: Compositional changes in saliva reflecting inflammation were found in the first days after HSCT, and the use of cryotherapy in the second part was associated with decreased OM severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…4). Several studies have demonstrated decreased salivary flow rate during APSCT under the influence of conditioning treatment 6 , in concert with our results (Fig. 4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…4). Several studies have demonstrated decreased salivary flow rate during APSCT under the influence of conditioning treatment 6 , in concert with our results (Fig. 4).…”
Section: Discussionsupporting
confidence: 92%
“…There is impairment of salivary antimicrobial defence and mucosal integrity during APSCT 6,49 . Thus, we can conclude that postmenopausal hormonal changes increase the risk of OM that occurs during APSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, despite the increased permeability of the glomerular filter in NS, capillary permeability of the salivary gland appears to be unaffected. Decreased serum protein levels correlate with changes in saliva composition that are evident in other diseases [10,11] and corroborate the intimate relation between serum and saliva characteristics. Furthermore, similar correlations have been shown between saliva and systemic markers for various conditions such as diabetes [8] and autoimmune disorders [9] in adults.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, despite the increased permeability of the glomerular lter in NS, capillary permeability of the salivary gland appears to be unaffected. Decreased serum protein levels correlate with changes in saliva composition that are evident in other diseases [10,11], and corroborate the intimate relation between serum and saliva characteristics. Furthermore, similar correlations have been shown between saliva and systemic markers for various conditions such as diabetes [8] and autoimmune disorders [9] in adults.…”
Section: Discussionsupporting
confidence: 72%